2009
DOI: 10.1111/j.1558-5646.2008.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

LEAF SHAPE EVOLUTION IN THE SOUTH AFRICAN GENUSPELARGONIUML’ HÉR. (GERANIACEAE)

Abstract: Leaf shapes reflect complex assemblages of shape-determining elements, yet evolutionary studies tend to treat leaf shape as a single attribute, for example cordate or linear. As with all complex structures, individual elements of a leaf could theoretically evolve independently and at different rates to the extent permitted by genetic and functional limitations. We examined relative evolutionary lability of shape-determining elements in the highly diverse South African plant genus Pelargonium (Geraniaceae).We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 69 publications
2
67
0
Order By: Relevance
“…1), often within growth forms and taxonomic sections. Parsing of leaf form categorically revealed that the extent of dissection of the blade is highly evolvable within an overall ovate leaf shape outline that is evolutionarily conserved (Jones et al 2009). …”
Section: Pelargoniummentioning
confidence: 99%
“…1), often within growth forms and taxonomic sections. Parsing of leaf form categorically revealed that the extent of dissection of the blade is highly evolvable within an overall ovate leaf shape outline that is evolutionarily conserved (Jones et al 2009). …”
Section: Pelargoniummentioning
confidence: 99%
“…Leaf boundary layer models predict leaf shape as a key element of plant thermoregulation (reviewed in Nicotra et al [16]), but leaf shape has largely been neglected in global leaf-climate analyses (but see [8,17]). Jones et al [18] recently provided the first explicitly phylogenetic analysis of leaf shape evolution, in South African Pelargonium. They found that leaf size and degree of dissection were evolutionary labile traits, but surprisingly, the overall outline of the leaf was fairly conserved.…”
Section: Introductionmentioning
confidence: 99%
“…Selection pressures from climate variation across a geographic range could lead to locally adapted populations (Linhart and Grant 1996), which could result in significant morphological diversification of a taxonomic group in an ecologically diverse region (e.g., Jones et al 2009;Mitchell et al 2015). Therefore, investigating whether climate is linked to plant morphological diversity could provide insight into the drivers of leaf variation among related plant species and possibly species divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Elements of leaf shape have been shown to be evolutionarily labile in ecologically diverse regions like the Cape Floristic Region (Jones et al 2009). Interestingly, environmental associations explained trait variation in closely related Protea species in South Africa, highlighting the potential role of evolutionary history in trait variation (Prunier et al 2012).…”
Section: Introductionmentioning
confidence: 99%